2012
DOI: 10.1021/ef3013129
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Properties of Asphaltene Solutions: Solvency Effect on Conductivity

Abstract: Electrical demulsification is considered an elegant method to enhance the separation of water-in-crude-oil emulsions. Understanding the mechanisms involved during this process remains a challenge for the further development of this separation method. The aim of this study is to elucidate the influence of the aggregation state of the asphaltenes on their conductivity, to determine the mechanisms governing conductivity in crude oils. Dielectric properties of two different asphaltenes extracted from crude oils (l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…In addition to being a technique with a relatively short path, most of the published studies on mixtures are reduced to binary systems. To the authors' knowledge, only a few of them address mixtures with more than two components [47,48,56,68]. It is clear that the application of the technique to samples of such complexity, such as diesel fuel and biodiesel, is a challenge.…”
Section: Excess Complex Dielectric Constantmentioning
confidence: 99%
“…In addition to being a technique with a relatively short path, most of the published studies on mixtures are reduced to binary systems. To the authors' knowledge, only a few of them address mixtures with more than two components [47,48,56,68]. It is clear that the application of the technique to samples of such complexity, such as diesel fuel and biodiesel, is a challenge.…”
Section: Excess Complex Dielectric Constantmentioning
confidence: 99%
“…It shows that the n ‐hexane addition can enhance the free water content in the oil sands mixture. The previous investigations have proven that an increasing free water content could enhance the soil mixtures’ permittivity . Hence, the dynamic change of free water content induced by the addition of n ‐hexane provides an explanation for the permittivity behaviours of n ‐hexane/oil sands mixtures.…”
Section: Resultsmentioning
confidence: 92%
“…Electrical conductivity (EC) represents the ability of material to conduct an electric current. EC measurements have been utilized to understand behavior of asphaltenes alone and their interactions with other crude oil components in different solvents. , It has been shown that the crude oils rich with asphaltenes had a higher conductivity than other oils . The conductivity of crude oil solution was suggested to be governed not only by the amount of asphaltenes in the crude oil but also by their aggregation state and mobility.…”
Section: Electrical Properties Of Asphaltenesmentioning
confidence: 99%
“…The crude oil diluted with heptane showed a lower conductivity than those same oils diluted with the same amount of toluene. The observation was ascribed to more pronounced aggregation of asphaltenes in heptane compared to toluene and the formation of larger aggregates. , Later, by comparing the DC conductivities at various concentrations of asphaltenes, it was concluded that the most aromatic components of crude oils are captured by toluene, in which they contribute to high conductivity, while the fractions of crude oils that form nanoaggregates are captured by n -heptane and are characterized by low conductivity . It has been also suggested that electrical conductivity may originate from a rapid charge exchange between asphaltene colloidal particles and that the self-association of asphaltenes in crude oil can be facilitated by the electron transfer between asphaltene molecules …”
Section: Electrical Properties Of Asphaltenesmentioning
confidence: 99%
See 1 more Smart Citation